Avaliação do efeito do gradiente de velocidade na agregação de partículas em unidades mistura completa e de fluxo pistonado - Manfio, Júlia Caetano (2018)
In order to increase the knowledge about flocculation, unitary operation relevant for the water and wastewater treatment, the main goal of this study was to evaluate comparatively the effect of the velocity gradient (G) in the formation of flocs, used in complete mixing units (CM) and plug flow aggregation units, in named coiled tubular flocculator (CTF), in terms of settling velocity, reduction of turbidity and color. Three aggregation units were evaluated for CM and three CTF units, in a semi-pilot scale, in order to compare and verify the influence of the G (500, 940 and 1381 s-1) on flocs formation, based on the variation of flocculator operating parameters (flow rates per minute of the mechanical agitation and diameter of the flocculators), with hydraulic detention times between 10 and 20 seconds. The monitoring of the aggregation efficiency was carried out at the end of the operation of each unit, in terms of settling rate of Fe(OH)3 flocs, turbidity and residual color. The results obtained in the evaluation of the clarification the CTF reached a reduction of 91.5% of the turbidity, while the CM units reduced 65.8% of the turbidity, applying the G of 940 s-1 and concentration of solids of 86 mg L-1. In the CTF, the majority of the tests had turbidity reduction above 80%, while in the CM only one flocculator presented a reduction of 81.9% with a G of 1381 s-1 and Fe(OH)3 concentration of 86 mg L-1. In the CTF most of the tests showed a reduction of color over 90%, while in the CM, only one flocculator, with a G of 1381 s-1 and Fe(OH)3 concentration of 86 mg L-1 presented reduction of 93, 5%. In the CTF most of the tests showed a reduction of color over 90%, while in the CM, only one flocculator, with a G of 1381 s-1 and Fe(OH)3 concentration of 86 mg L-1 presented reduction of 93,5%. The evaluation of the G as a function of settling speed showed that in the CTF the higher G impaired the formation of the flocs, resulting in a lower settling velocity of the flocs and less removal of turbidity and color. In this flocculator model, high G values result in aggregate rupture. For the CM units, the increase of the G favored the formation of the flocs, increasing settling velocity, turbidity, and color removal, possibly due to the number of Camp, which, for low hydraulic holding times, requires a higher turbulence dissipation energy. The CTF showed efficiency in the floc generation higher than the CM units, confirming that the G influences the aggregation of particles in the plug flow units and CM units, considering the short hydraulic holding time (10 to 20 seconds).